2017
DOI: 10.1590/1807-1929/agriambi.v21n8p550-555
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption kinetics of damaged beans: GAB model

Abstract: The objective of this study was to model the water sorption kinetics of damaged beans. Grains with initial moisture content of 53.85%, dry basis (d.b.), were used. One portion of the grains was used to obtain desorption isotherms, while the other was subjected to drying until the moisture content of 5.26% (d.b.), so that it was subjected to the adsorption. For the induction of damage, a Stein Breakage Tester was used. To obtain the equilibrium moisture content, grains were placed in a climatic chamber at 20, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
4
5
0
Order By: Relevance
“…In a previous study by the same research group (Baptestini et al, 2017), it was found that the Guggenheim-Anderson-de Boer (GAB) model satisfactorily described the equilibrium moisture content of the damaged beans at the same conditions used in the present study. Therefore, water activity was calculated using the GAB model, which is required to obtain the thermodynamic properties as described below.…”
Section: Methodssupporting
confidence: 71%
“…In a previous study by the same research group (Baptestini et al, 2017), it was found that the Guggenheim-Anderson-de Boer (GAB) model satisfactorily described the equilibrium moisture content of the damaged beans at the same conditions used in the present study. Therefore, water activity was calculated using the GAB model, which is required to obtain the thermodynamic properties as described below.…”
Section: Methodssupporting
confidence: 71%
“…Analyzes of Figure 3, shows that hysteresis magnitudes decrease as temperature increases, as verified by different authors (Bejar et al, 2012;Corrêa et al, 2014;Souza et al, 2015;Goneli et al, 2016;Baptestini et al, 2017b;Torres et al, 2018). However, hysteresis values at 30 ºC were higher than hysteresis at 20 ºC, at the water activity interval between 0.3 and 0.4, probably due to the elasticity increase of the capillary walls.…”
Section: Figure 1 Chung Pfost Model Residual Values For Desorption (A) and Adsorption (B) Of Paddy Rice Grainssupporting
confidence: 70%
“…This might be a result of hardening of the surface because of the high rate of evaporation from the surface of food compared to diffusion from the interior of food. This leads to change in physical structure of foods 41 . These findings are consistent with the results documented by Muzaffar and Kumar 27 for tamarind pulp powder and Alamri et al 42 .…”
Section: Discussionsupporting
confidence: 91%